Relationship between the Role of Nursing Educators with Compliance and Lung Tuberculosis Control Patients in Medika Mulia Hospital - Citra Dewi Ayu Trisnawati (STKIP Singkawang, 2020)
The compliance control of Lung Tuberculosis patients to Poli Paru is influenced by several factors one of which is the Hospital environmental factors (doctors, nurses, midwives, and other health teams). Nurses are a profession very close to patients, one of the approaches used by nurses is the role of the nurse as an Educator. The purpose of this study was to know the relationship between the role of the Nurse Educator with the compliance control of pulmonary tuberculosis patients in Medika Mulia Hospital, Tuban. The method used in this research was the correlation analytic method with a cross-sectional research design. The research in this study involved 66 pulmonary TB patients in Pulmonary Medika Mulia Hospital of Tuban with the determination of the sample using a systematic random sampling method. Data collection was carried out by questionnaire using Spearman rho test data analysis. From the results of the analysis obtained data with a significance value of 0.003 (p <0.05) which means there was a positive relationship between the role of Educator nurses with compliance with Lung Tuberculosis patient compliance. Therefore, HI was accepted, namely the close relationship between the role of the Educator nurse and the compliance control of Lung Tuberculosis patients in the Pulmonary Poli Medika Mulia Hospital, Tuban. The results of this study provided input to nurses in the development of nursing knowledge, specifically the role of nurses as educators in the Pulmonary Poli Medika Mulia Hospital of Tuban to improve control compliance in pulmonary TB patients.